Countertopographies of Migrant Women: Transnational Families, Space, and Labor as Solidarity. Issue 3 (September 2014) - Francisco, Valerie; Rodriguez, Robyn Magalit
<x xml:space="preserve">Abstract</x> Through our analysis of the domestic workers' lives in New York City and Hong Kong, we explore how Filipina migrants make transnational connections, how these connections operate, and when these connections act as a basis for transnational mobilization. We find that, although Filipina migrant workers experience very different working and living conditions, they similarly engage in transnational solidarity organizing with and for one another across their migrant locations. Further, the subjectivities through which they engage in cross‐border activism can take parallel forms. We find that migrant women's experiences of gendered social reproductive labor, both paid and unpaid, are salient in shaping their political subjectivities, and they connect these experiences to a critique of their "home" state.